Death sentence for drug traffickers: to uphold or to abolish / Jasmee Hameeza Jaafar, Norhani Mohd Adzhar, Nurafinie Mohd Fadzly - Jaafar, Jasmee Hameeza; Mohd Adzhar, Norhani; Mohd Fadzly, Nurafinie (2006)
This research is about the punishment of death penalty for the drug trafficking offences. The main issue to be discussed in this research is whether death penalties for drug trafficking should be uphold or abolished. This research includes the idea that will discuss the problems and issues that arose by imposing death penalty for drug traffickers through discussion from books, journal, material and scholar's perceptions, which are related to the topic. This research also discuss the historical background of death penalty in Malaysia and the amendment in Section 39B Dangerous Drugs Act 1952 and how it relates to death sentence also discussing the issues whether death penalty can deter the serious crime and also the study regarding the effectiveness of death penalty in deterring the crime. We have also done a research regarding the issues whether the death penalty is considered as barbaric form of punishment in modern society and whether it is acceptable by the people.